Questioning Government Public Policies toward Indonesian Stateless Children in Malaysia - Irsyad Dhahri Samad; Risma Niswati; Rasmidar Samad; Laelah Azizah; Mushawwir Thaiyeb (Universitas Padjadjaran, 2023)
Millions of stateless statuses existed around the world, half of them are scattered in Asia expanding across several regions. The status and situation of the Indonesian stateless are so complex and to construe this situation causing the government to strengthen policies in protecting their rights is questioned. The purpose of this article is to observe how effective the implementation of Indonesian policies in protecting Indonesian stateless children who currently spread in several regions of Malaysia. The research was conducted in qualitative method approach on several legal and human rights provision added with field interviews, data collections and observations. As the issue is considered essentially for both Malaysian and Indonesia Governments and conditions surrounding the topic have complex multifaceted problems, struggles of law and political effort in line with economy and social hindrances that continually hinge around should be enforced. The result shows that more implications on the protection of rights for stateless children need to be persistently strengthened by using existing various conventions and governmental regulations. Also, social economic and political conditions in Indonesia and Malaysia are different making soluble alternative that fit countries needs is not tranquil to have.